The Effect of Human Resources Competencies and Internal Controlling System on the Quality of Accounting Information System and Their (Asian Journal of Social Science Studies, 2021)
This study aims to determine the effect of human resources competencies and internal controlling systems on the quality of accounting information systems and to deter-mine the quality of financial reporting. This study is a quantitative study with primary data obtained from 105 respondents from the finance/administration/budget division of the DKI Jakarta Provincial Government SKPD who collected 52 SKPD. Partial Least Square is used as an analytical tool in this study. The results showed that the competence of human resources and internal controlling systems directly have a significant effect on the quality of accounting information systems and the quality of accounting information systems have a significant effect on the quality of financial reporting.